Developing Spatial Thinking Competence and Sustainability Awareness through Geography Learning: A Systematic Literature Review - Analisman Roi Lase; Najma Nur Mawaddah; Rahmadi Rahmadi; Juwari Juwari (Abjadia : International Journal of Education, 2026)
Spatial thinking and sustainability awareness are essential competencies in geography education, particularly in addressing global environmental challenges. However, the development of these competencies among students remains suboptimal and is strongly influenced by the learning approaches employed. This study aims to analyze 12 scientific articles related to the development of spatial thinking skills and sustainability through geography learning. This study adopts a Systematic Literature Review (SLR) method using the PRISMA approach to ensure a systematic, transparent, and reproducible selection process. Articles were selected based on topic relevance, publication year (2016–2026), and alignment with the research focus. The findings indicate that the most dominant and effective learning models in enhancing spatial thinking skills are Problem-Based Learning (PBL) and Project-Based Learning (PjBL), followed by the Earthcomm model, which emphasizes real-world environmental contexts. In addition, the integration of geospatial technologies such as Geographic Information Systems (GIS), Google Earth, and ArcGIS has been shown to significantly improve students’ spatial analysis, representation, and reasoning abilities. These approaches not only enhance spatial thinking skills but also strengthen students’ awareness of sustainability issues. Therefore, the combination of innovative learning models and geospatial technology integration represents an effective strategy for supporting the development of spatial thinking and sustainability competencies in geography education.